Formation of financial literacy of schoolchildren in the process of solving competent oriented tasks in the course of mathematics of a basic school - Ekaterina Mikhailovna Natyrova (Вестник Майкопского государственного технологического университета)
The article reveals the relevance of the formation of financial literacy of schoolchildren in the process of learning Mathematics, due to the global financial crisis, complication of financial activity and inability of a significant part of the population to make decisions related to the use of financial instruments to improve the life quality. Financial literacy is seen as the ability to manage personal finances effectively, keep track of household expenses and incomes, carry out short-term and long-term financial planning, make informed decisions about financial products and services and be responsible for them. Its structure includes personal characteristics, financial competencies and socio-economic roles. The research problem is associated with the disclosure of the potential of a basic school Mathematics course in the formation of students' financial literacy. The purpose of the study is to justify and develop competency-oriented tasks that ensure the formation of financial literacy of students in the course of Mathematics in primary school. During the study, a complex of theoretical and experimental methods have been used, which include analysis of literary sources, modeling, design, data generalization, observation and interrogation. A three-component structure of competency-based tasks based on a combination of context, competency framework and social roles has been developed.